Pendampingan Praktek Magang Pada Dinas Perumahan Rakyat dan Kawasan Permukiman Kabupaten Timor Tengah Selatan Oleh Mahasiswa Program Studi Manajemen dan Ekonomi Pembangunan Universitas Timor - Fredirikus Timo; Yeremias Lake; Bernadus Ghawa Rado; Marlinda Pala Bani; Rikhardus Bria Seran (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Community service is carried out by providing internship assistance at the Public Housing and Settlement Areas Service, South Central Timor Regency. This practical internship activity aims to provide opportunities for students to apply theory and knowledge during lectures to practical realities in the world of work. The method used is Field Work Practice at the Public Housing and Settlement Department, South Central Timor Regency. Mentoring was carried out for 4 students with an effective period of 40 working days. The results of the internship work practice are that interns can learn directly about the financial realization of the settlement development program, settle incoming and outgoing letters, prepare accessories to repair pipes that are still leaking